Day of the Dead in the USA : the migration and transformation of a cultural phenomenon - Marchi, Regina M., 1965- (Latinidad., 2009)
Honoring relatives by tending graves, building altars, and cooking festive meals has been an honored tradition among Latin Americans for centuries. The tribute, "el Dia de los Muertos," has enjoyed renewed popularity since the 1970s when Latino activists and artists in the United States began expanding "Day of the Dead" north of the border with celebrations of performance art, Aztec danza, art exhibits, and other public expressions. Focusing on the power of ritual to serve as a communication medium, Regina M. Marchi combines a mix of ethnography, historical research.